Design Of Navigation Algorithm For F_Bot For Patrolling Using Fuzzy Logic - Yusof, Ahmad Ashaari (Universiti Sains Malaysia, 2006)
The main objective of this project is to build a mobile robot that would be able to navigate from one position to the other assigned position. It is also able to determine the shortest path towards the goal position without hitting any obstacle along the path. This mobile robot uses the Fuzzy Logic controller to navigate the robot in varying environments to a specified position. The implementation has been carried out using inexpensive components and tools. As the mobile robot is using the fuzzy logic controller to control its movement, it is named as F_Bot The F_Bot has two front wheels navigated by two servo motors 5V and a free castor wheel is placed at front. The robot will be moving towards the specified goal position determined by the user by using the dead reckoning method. The data acquisition is done by the PIC microcontroller from various sensors including ultrasonic range detector sensor, infrared sensor and encoder. The data will be sent to the computer using serial data transmission method. The data will be processed by the computer using Matlab and Fuzzy Logic to get the correct angle and the acceleration for the robot. This data will be sent back to the PIC microcontroller to control the motors for navigation purposes. The servo motors are easily controlled by feed-in pulses directly from the PIC microcontroller. The PIC microcontroller 16F877 can perform a large number of applications especially for control and sensing applications. In addition, MATLAB is a standard and cost- effective tool within the engineering community for scientific applications. The Fuzzy Logic is used here to predict the direction of movement and the speed for the robot. Since the input data for predicting the direction and speed is too large, the fuzzy logic is used for fast prediction.